2018
DOI: 10.1111/aos.13683
|View full text |Cite
|
Sign up to set email alerts
|

Age‐related changes in with‐the‐rule and oblique corneal astigmatism

Abstract: Corneal astigmatism is stable until the age of 50 years; thereafter both keratometric and total corneal astigmatism show a 0.25 D ATR change per 10 years. The average 0.25 D ATR PCA compensates the predominant keratometric WTR astigmatism in the younger patients and increases the TCA in the elderly with keratometric ATR astigmatism. The gender-based differences in age-related astigmatism require further studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
35
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 26 publications
7
35
1
Order By: Relevance
“…Other studies with wider age ranges reported greater changes in these indices. 38,39 In agreement with other studies, 4042 our results indicated that females have more steep corneas. In contrast, Cheung et al 43 reported similar Q-values for the two genders, although the small sample size (63 subjects) and low power may be responsible for the non-significant inter-gender difference.…”
Section: Discussionsupporting
confidence: 93%
“…Other studies with wider age ranges reported greater changes in these indices. 38,39 In agreement with other studies, 4042 our results indicated that females have more steep corneas. In contrast, Cheung et al 43 reported similar Q-values for the two genders, although the small sample size (63 subjects) and low power may be responsible for the non-significant inter-gender difference.…”
Section: Discussionsupporting
confidence: 93%
“…In the present multicenter study, we found a mean PCA of 0.34 ± 0.14 D with a range of 0.00 D-0.99 D in Chinese myopic patients having corneal refractive surgery. The result was consistent with previous studies showing a mean PCA of 0.24 D-0.37 D in healthy eyes from subjects of the similar ages 9,15,16,24 . In our study, PCA ≥ 0.50 D was found in 11.61% of the eyes.…”
Section: Discussionsupporting
confidence: 93%
“…There have been several reports about PCA pattern in patients having assessment for refractive surgery or in patients about the same age 9,15,16 . However, results from these reports may not be directly applied to our patients since there may be significant differences in posterior corneal metrics among different ethnic groups 17 .…”
mentioning
confidence: 99%
“…This may be partly explained by the fact that the hyperopic group was significantly older than the myopic group and, therefore, may have underwent natural change of the astigmatism vector toward against-the-rule as corneas and associated refraction tend to shift from with-the-rule to against-the rule while aging. 17 In the current study, an association between age and corneal thickness was non-existent for myopes and negligible for hyperopes. Conflicting reports have been published regarding the association between age and corneal thickness with thinning of the cornea at a rate of up to 7 μm per decade being been reported by some groups, [18][19][20][21] and others reporting no such association.…”
Section: Discussioncontrasting
confidence: 51%